Pelvic trauma mortality reduced by integrated trauma care. (14th June 2017) - Fitzgerald, Mark; Esser, Max; Russ, Matthias; Mathew, Joseph; Varma, Dinesh; Wilkinson, Andrew; Mannambeth, Rejith V; Smit, Devilliers; Bernard, Stephen; Mitra, Biswadev
Abstract: Objectives: A multidisciplinary approach that emphasised improved triage, early pelvic binder application, early administration of blood and blood products, adherence to algorithmic pathways, screening with focused sonography (FAST), early computed tomography scanning with contrast angiography, angio‐embolisation and early operative intervention by specialist pelvic surgeons was implemented in the last decade to improve outcomes after pelvic trauma. The manuscript evaluated the effect of this multi‐faceted change over a 12‐year period. Methods: A retrospective cohort study was conducted comparing patients presenting with serious pelvic injury in 2002 to those presenting in 2013. The primary exposure and comparator variables were the year of presentation and the primary outcome variable was mortality at hospital discharge. Potential confounders were evaluated using multivariable logistic regression analysis. Results: There were 1213 patients with a serious pelvic injury (Abbreviated Injury Scale ≥3), increasing from 51 in 2002 to 156 in 2013. Demographics, injury severity and presenting clinical characteristics were similar between the two time periods. There was a statistically significant difference in mortality from 20% in 2002 to 7.7% in 2013 ( P = 0.02). The association between the primary exposure variable of being injured in 2013 and mortality remained statistically significant (adjusted odds ratio 0.10; 95% confidence interval: 0.02–0.60) when adjusted for potential clinically important confounders. Conclusions: Multi‐faceted interventions directed at the spectrum of trauma resuscitation from pre‐hospital care to definitive surgical management were associated with significant reduction in mortality of patients with severe pelvic injury from 2002 to 2013. This demonstrates the effectiveness of an integrated, inclusive trauma system in achieving improved outcomes.